Биология каштановой минирующей моли Cameraria ohridella (Lepidoptera, Gracillariidae) в Украине. Сообщение 1 - Акимов, И.А.; Зерова, М.Д.; Нарольский, Н.Б.; Свиридов, С.В.; Коханец, А.М.; Никитенко, Г.Н.; Гершензон, З.С. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2003)
Приведены данные по биологии и фенологии имаго и преимагинальных фаз каштановой моли 1-го поколения для Украины. Обсуждается таксономический статус рода Cameraria. Описываются стадии образования мин, с целью определения возраста гусениц непосредственно в полевых условиях. Рассчитаны суммы эффективных температур начала лета имаго и продолжительности развития 1-й генерации моли. Приведены особенности поведения имаго моли, характерные только для 1-го поколения. Указаны сведения о 3 видах наездников-хальцид, выведенных из моли. Уточнен год появления моли в Украине и приведена карта ареала. There data on biology and phenology of imaginal and preimaginal stages of the chestnut leafminer moth Cameraria ohridella of the 1st generation are present for Ukraine. The taxonomic status of the genus Cameraria is discussed. Stages of mines formation are described, with in order to define the age of caterpillars directly in field conditions. The sums of effective temperatures needed to complete the larval development and durations of development of the 1st generation of this moth are designed. Features of the imago peculiar only for the 1st generation are summarised. Data on 3 species of chalcid-wasps reared from the moth are specified. The year of the moth appearance in Ukraine is specified and the map of its range is provided.